ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI JARAK BERANAK (Calving Interval) SAPI BALI DI KECAMATAN BANGKINANG KABUPATEN KAMPAR - Mawaddah Ridha; Hidayatid dan; Triani Adelina (Jurnal Peternakan, 2007)
To increase growth rate of population Bali cattle in the area can be done with efficient of calving interval markers with high calving rate. The aim of this research was to analyze factors which influencing calving interval of Bali Cows in Bangkinang District Data was collected using simple random sampling with accidental sampling technique on 161 head Bali Cows as a sample, into Laboy Jaya Village 48 head, Suka Maju Village 59 head, Bukit Sembilan Village 23 head and Bukit Payung Village 36 head. The result of this research was showed that length of pregnant (Xl), weaning age (X2) and first service after calving (X4) was influenced calving interval of Bali Cows in Bangkinang District.